(untitled) (Research, Society and Development, 2021)
Pandora’s Syndrome is a disorder in the lower urinary tract of felines, its pathogenesis is not fully understood, but it is known that there are predisposing factors to its appearance, such as: genetic, low water intake, environmental stress, obesity, life modern cat household and lack of physical activity. The objective of this work was to report the main information described about this condition, in addition to its impact on the organism in these animals. Thus, articles were searched in document, article and book indexing databases, such as Scielo, Google Scholar, Pub Med and Scopus in the last 11 years, seeking more relevant and recent information about the disease. The syndrome presents itself in a complex form that presents nonspecific clinical signs, making its diagnosis very difficult, requiring the use of several laboratory tests. Treatment involves multimodal therapy with environmental management, promotion of environmental enrichment, reduction of stressors that may affect the animal. Furthermore, this disease has a negative impact on animal abandonment, as animals with the Syndrome tend to suffer abandonment. Therefore, studies on this change are important for updating professionals, allowing them to promote the well-being and better life expectancy of their patients, in addition to making tutors aware of the disease.